The Development of Greenfield Projects in the World - Pohrebskyi, Taras H. (Волинський національний університет імені Лесі Українки, 2025)
The term “greenfield projects” was originally used to describe сonstruction processes of production complexes within suburban or agricultural areas in the early XX century in Great Britain. In 1966 above 10% of all England’s manpower worked in industrial enterprises. All this contributed to territorial differentiation stability of country’s economic development. Apart from that, world economy recession in 1930s and further economic decline indicators as a result of World War II events encouraged developed countries to adopt regional development policy. This policy attracts foreign investments in the establishment of branch networks in less developed regions emphasizing benefits of greenfield projects as the catalyst for depressed areas’ economic growth. Particularly, during 1954–1982 French government developed a new regional development policy of the country. This policy provided tax benefits for enterprises which would be relocated from the Paris region urbanized areas into less developed agricultural territories in the West and South-West of the country. This has led to jobs growth in industrial sector and number of jobs reached for about 368 thousand vacancies
Keywords: Projects; Greenfield Projects; Greenfield Projects in the World; 911.3(100)1